States and women's rights : the making of postcolonial Tunisia, Algeria, and Morocco - Charrad, M. (Mounira) (Berkeley : University of California Press, 2001)
At a time when the situation of women in the Islamic world is of global interest, here is a study that unlocks the mystery of why women's fates vary so greatly from one country to another. Mounira M. Charrad analyzes the distinctive nature of Islamic legal codes by placing them in the larger context of state power in various societies. Charrad argues that many analysts miss what is going on in Islamic societies because they fail to recognize the logic of the kin-based model of social and political life, which she contrasts with the Western class-centered model. In a skillful synthesis, she shows how the logic of Islamic legal codes and kin-based political power affect the position of women. These provide the key to Charrad's empirical puzzle: why, after colonial rule, women in Tunisia gained broad legal rights (even in the absence of a feminist protest movement) while, despite similarities in culture and religion, women remained subordinated in post-independence Morocco and Algeria. Charrad's elegant theory, crisp writing, and solid scholarship make a unique contribution in developing a state-building paradigm to discuss women's rights.
Similarities: Common Heritage of the Maghrib -- State Formation in Kin-Based Societies -- States, Nations, and Local Solidarities -- Central/Local Tension in the History of the Maghrib -- The "Republics of Cousins" in Politics -- Islam and Family Law: An Unorthodox View -- The Law in Islam -- Islamic Family Law -- Customary Law -- Women Ally with the Devil: Gender, Unity, and Division -- Men as Unity -- Women as Division -- Marriage Alliances: Ideology and Reality -- Veils and Walls -- Men Work with Angels: Power of the Tribe -- Ties That Bind: Tribal Solidarity -- Tribes, Islamic Unity, and Markets -- Tribes and Central Authority -- Historical Differences -- The Precolonial Polity: National Variations -- Tunisia: Early Development of Centralized Institutions -- Algeria: Tribal Isolation and Weak State -- Morocco: Land of Government Versus Land of Dissidence -- Family Law as Mirror of the Polity -- Colonial Rule: French Strategies -- Form of Colonial Domination -- Colonial Manipulation of Family Law -- Three Paths to Nation-State and Family Law -- Palace, Tribe, and Preservation of Islamic Law: Morocco -- Coalition between Palace and Tribe (1940s-50s) -- Islamic Family Law Preserved: Choice of the Monarchy (1950s) -- Elite Divisions and the Law in Gridlock: Algeria -- Partial Reliance on Kin-Based Groups (1950s-60s) -- Family Law Held Hostage to Political Divisions (1950s-80s) -- State Autonomy from Tribe and Family Law Reform: Tunisia -- State Autonomy from Tribes (1930s-50s) -- The Transformation of Family Law (1930s-50s).
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women's rights -- Africa, North -- History; Muslim women -- Government policy -- Africa, North -- History; Domestic relations (Islamic law) -- Africa, North -- History; Tribes -- Africa, North -- History; Africa, North -- Politics and government; Musulmanes -- Politique gouvernementale -- Afrique du Nord -- Histoire; Tribus -- Afrique du Nord -- Histoire; Femmes -- Droits -- Afrique du Nord -- Histoire; Familles (Droit islamique) -- Afrique du Nord -- Histoire; Afrique du Nord -- Politique et gouvernement; Musulmanes -- Politique gouvernementale -- Afrique du Nord -- Histoire; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Domestic relations (Islamic law); Muslim women -- Government policy; Politics and government; Tribes; Women's rights; North Africa; Vrouwen; Mensenrechten; Nationaal recht; Islamieten; Femmes -- Droits -- Afrique du Nord; Musulmanes -- Conditions sociales -- Afrique du Nord; Famille -- Droit islamique -- Afrique du Nord; Afrique du Nord -- Politique et gouvernement -- 20e siècle.; Droit islamique; Droits de la femme; Histoire; Musulman; Politique gouvernementale; Tribu; Afrique du Nord; Algérie.; Maroc; Tunisie; History; Electronic books